(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kucher S. The composition of the Ukrainian national clothes as a source of learning the basics etnodizayna. The article reveals problems familiarize future teachers with the technology of special features of national design. One of the parties of design based on ethnic associated with the creation of clothing, it is proposed to studyin three phases: 1) an introduction to the composition of the national costume, and 2) the manufacture of traditional clothing, based on a centuries-old technology, and 3) the transformation of ideas of Ukrainian folkdressin the design of modern costume and accessories.